Trips Agreement Dan Standarisasi Hukum Perlindungan Hak Kekayaan Industri Di Indonesia - Rani Fadhila Syafrinaldi; David Hardiago (UIR Press, 2021)
Trade Related Aspects of Intellectual Property Right Agreement 1995 (TRPS Agreement) is an international provision in the field of intellectual property rights protection that applies universally. Indonesia as a country of law, has all laws relating to the protection of intellectual property rights with reference to the TRIPS Agreement. The TRIPS Agreemnt formulation must also refer to the Paris Convention For the Protection of Industrial Property, 1883 which has been recognized as the legal basis for the protection of intellectual property rights globally. Protection of industrial assets consisting of Patents, Trademarks, Trade Secrets, Industrial designs, Protection of Plant Varieties and Layout Designs of Integrated Circuits must be carried out by the state towards the holders of the said industrial property rights